The dynamics of short- and long-term CDS-spreads of banks - Thomas Almer; Thomas Heidorn; Christian Schmaltz (Frankfurt School of Finance & Management, 2008)
This paper studies 'Stylised Facts' and 'Determinants' of short-and long-term CDS-spreads of banks. As short-term spreads we choose 6M-, as long-term spreads we choose 5Y-spreads. In the section 'Stylised Facts' we found that the correlation between short-and long-term spreads for the total period is high (97%). However, the correlation in sub-periods varies across all possible correlations. Particularly, spreads can have negative correlation. In contrast to [Covitz and Downing, 2007], we find high positive (Covitz/Downing: high negative) correlation for turbulent market circumstances. In the section 'Deteminants' we confirm the Merton-factors (stock price, stock price volatility, interest rate level) for the 5Y-segment, but not for the 6M-segment. Furthermore, we do not find any empirical support that short-term spreads are particularly sensitive to illiquidity factors. In that sense, we also contrast [Covitz and Downing, 2007].
urn:nbn:de:101:1-2008090112
Keywords: G32; 330; Liquidity; insolvency; banks